2021
DOI: 10.1038/s41598-021-82317-x
|View full text |Cite
|
Sign up to set email alerts
|

A two dimensional semi-continuum model to explain wetting front instability in porous media

Abstract: Modelling fluid flow in an unsaturated porous medium is a complex problem with many practical applications. There is enough experimental and theoretical evidence that the standard continuum mechanics based modelling approach is unable to capture many important features of porous media flow. In this paper, a two-dimensional semi-continuum model is presented that combines ideas from continuum mechanics with invasion percolation models. The medium is divided into blocks of finite size that retain the nature of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 67 publications
(116 reference statements)
1
24
0
Order By: Relevance
“…At low initial water saturations, the displacements are characterized by well-defined fingering patterns. However, the fingers grow slower and wider at fully saturated conditions, disappearing in a diffusion-like displacement front, as pointed out by Kmec et al [ 69 ].…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…At low initial water saturations, the displacements are characterized by well-defined fingering patterns. However, the fingers grow slower and wider at fully saturated conditions, disappearing in a diffusion-like displacement front, as pointed out by Kmec et al [ 69 ].…”
Section: Resultsmentioning
confidence: 58%
“…This change in the flow patterns is attributed to a transition to a diffusion-like regime at increasing initial water saturations, causing a wider and broader water front. This feature has been characterized at the microscale on experimental and numerical studies of Viscous Fingering [ 68 , 69 ]. At low initial water saturations, the displacements are characterized by well-defined fingering patterns.…”
Section: Resultsmentioning
confidence: 99%
“…As soon as 1989, Glass and Yarrington 15 proposed a cellular automaton under the title of "mechanistic modelling", or "Macro Modified Invasion Percolation". In Kmec et al 16,42 , the authors introduced a semi-continuum model which will be described in this section. Let us consider a long narrow vertical test tube of cross-section A [m 2 ] and height L [m] filled with homogeneous and isotropic porous medium.…”
Section: Semi-continuum Modelling Of Porous Media Flowmentioning
confidence: 99%
“…However, none of these modifications is able to reproduce all the observed features of finger-flow 2 . A different attempt to overcome these drawbacks is the combination (3A) proposed in 15,16,41,42 . It has been shown that some of these models describe diffusion-like flow, finger-like flow, and the transition between the two regimes 16,42 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, especially in the field of soil physics and soil hydrology, many attempts were made to modify the RE so that it may also capture finger-like flow 34 44 . Another attempt is the combination (3A) proposed in 4 , 18 , 45 , 46 . It has been shown that some of these models describe diffusion-like flow, finger-like flow, and the transition between the two regimes 4 , 46 .…”
Section: Introductionmentioning
confidence: 99%